PAJAK PENGHASILAN ATAS PENGHASILAN DARI USAHA JASA KONSTRUKSI: DAHULU DAN KINI - Tansuria, Billy Ivan (JBE (Journal of Business and Economics); Volume 7 No.2, 2008 JBE UNKLAB, 2008)
Taxation of construction service in Indonesia has changed as business efforts, including construction service, have grown rapidly. The objective of this paper is to discuss the detailed ways of income taxation imposed on construction service business in Indonesia, which is found in Article 4 (2) and Article 23 of Law of The Republic of Indonesia Number 7 of 1983 Concerning Income Tax (UU No.7/1983), Government Regulation Number 140 of 2000 (PP No. 140/2000), PER-70/PJ/2007, and its comparison with Article 4 (2) and Article 23 of Law of The Republic of Indonesia Number 36 of 2008 Concerning Income Tax (UU No.36/2008) and Government Regulation Number 51 of 2008 (PP No. 51/2008). It also discusses further regulations which are still questioned and new regulation which is found in PP No. 51/2008 but is not found in previous government regulations regarding income tax of construction service business.